Determining Infiltration Rate from Infiltration Measurement with Flooding Method by Turftech Infiltrometer - Khaerudin, D Noorvy; Primantyo, Andre; Rahardika, Ryan (Civil and Environmental Science Journal (CIVENSE), 2019)
The density of the soil in this study estimate parameters with a dry bulk density. variation of soil density based on urban land us and then grouped into heavy, medium, and high-density soil. the rate of infiltration testing is performed by using turftech infiltrometer. and then analyzed with an infiltation horton modification models. the specification of turftech double ring infiltrometer are 6.03 cm for inner ring diameter and 10.79 cm for outer ring diameter. the result of infiltration rate observations is infiltration rate for higher density soil and land slope had low influences. the results showed that the turftech ifiltrometer that is used produced well results with 87% accuracy compared with the horton equation infiltration rate model. for the measurement results feasibility, then the turftech infiltrometer unable to represent for the land slope and density, because from the regression test the relationship between land slope and density toward infiltration rate was not significant and obtained average of 38% from the obtained r2.